Municipal Solid Waste Characterization according to Different Income Levels: A Case Study - Ozcan, Huseyin Kurtulus; Guvenc, Senem Yazici; Guvenc, Lokman; Demir, Goksel (MDPI, 2016)
Solid waste generation and characterization are some of the most important parameters which affect environmental sustainability. Municipal solid waste (MSW) characterization depends on social structure and income levels. This study aims to determine the variations in waste components within MSW mass by income levels and seasonal conditions following the analysis conducted on the characterization of solid wastes produced in the Kartal district of the province of Istanbul, which is the research area of this study. To this end, 1.9 tons of solid waste samples were collected to represent four different lifestyles (high, medium, and low income levels, and downtown) in the winter and summer periods, and characterization was made on these samples. In order to support waste characterization, humidity content and calorific value analyses were also conducted and various suggestions were brought towards waste management in line with the obtained findings. According to the results obtained in the study, organic waste had the highest rate of waste mass by 57.69%. Additionally, significant differences were found in municipal solid waste components (MSWC) based on income level. Average moisture content (MC) of solid waste samples was 71.1% in moisture analyses. The average of calorific (heating) value (HHV) was calculated as 2518.5 kcal.kg(-1).
Keywords: municipal solid waste (MSW); characterization; sustainability; waste management; MANAGEMENT; PERFORMANCE; GENERATION; TURKEY; QUANTIFICATION; SYSTEM; CHINA; CITY; MSW; Science & Technology - Other Topics; Environmental Sciences & Ecology